Sex‐specific effects of maternal weight loss on offspring cardiometabolic outcomes in the obese preeclamptic‐like mouse model, BPH/5 - Kalie F. Beckers; Christopher J. Schulz; Juliet P. Flanagan; Daniella M. Adams; Viviane C.L. Gomes; Chin‐Chi Liu; Gary W. Childers; Jenny L. Sones (Physiological Reports, 2022)
Abstract Preeclampsia (PE) is a hypertensive disorder that impacts 2–8% of pregnant women worldwide. It is characterized by new onset hypertension during the second half of gestation and is a leading cause of maternal and fetal morbidity/mortality. Maternal obesity increases the risk of PE and is a key predictor of childhood obesity and potentially offspring cardiometabolic complications in a sex‐dependent manner. The influence of the maternal obesogenic environment, with superimposed PE, on offspring development into adulthood is unknown. Obese BPH/5 mice spontaneously exhibit late‐gestational hypertension, fetal demise and growth restriction, and excessive gestational weight gain. BPH/5 females have improved pregnancy outcomes when maternal weight loss via pair‐feeding is imposed beginning at conception. We hypothesized that phenotypic differences between female and male BPH/5 offspring can be influenced by pair feeding BPH/5 dams during pregnancy. BPH/5 pair‐fed dams have improved litter sizes and increased fetal body weights. BPH/5 offspring born to ad libitum dams have similar sex ratios, body weights, and fecal microbiome as well as increased blood pressure that is reduced in the dam pair‐fed offspring. Both BPH/5 male and female offspring born to pair‐fed dams have a reduction in adiposity and an altered gut microbiome, while only female offspring born to pair‐fed dams have decreased circulating leptin and white adipose tissue inflammatory cytokines. These sexually dimorphic results suggest that reduction in the maternal obesogenic environment in early pregnancy may play a greater role in female BPH/5 sex‐dependent cardiometabolic outcomes than males. Reprograming females may mitigate the transgenerational progression of cardiometabolic disease.